The Phenomenon of Online Open Booking (BO) and Free Sex: A Hermeneutical Perspective of Double Movement in the Qur'an, Surah Al-Isra’: 32 - Arief Aljanandi; Ikhwanudin Ikhwanudin; Muhammad Agus Mushodiq (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the phenomenon of Open Online Booking (BO) and casual sex among adolescents from the perspective of the Qur'an, Surah Al-Isra': 32, using Fazlur Rahman's Double Movement Hermeneutics approach. The method used is qualitative with a descriptive-analytical approach based on literature study, utilizing primary sources from the Qur'an, interpretations, and related scientific literature. The results show that the prohibition of adultery in Surah Al-Isra': 32 is not only legal but also contains a preventative moral value, namely avoiding anything that leads to adultery. The resulting values include self-control, respect for human dignity, social empathy, and responsibility in relationships. These values are reinforced by Surah An-Nur: 30 of the Qur'an, which emphasizes the importance of maintaining one's perspective and self-respect. This study concludes that the moral values of the Qur'an remain relevant in addressing modern phenomena such as Open Online Booking and casual sex. Fazlur Rahman's Double Movement Hermeneutics approach is able to bridge the text with the context, resulting in a contextual and applicable moral understanding.